The air quality Model Documentation System of the European Environment Agency. (1st January 2000) - Moussiopoulos, N.; Leeuw, F. de; Karatzas, K.; Bassoukos, A.
With the aim of providing objective, reliable and comparable information on air pollution models, the European Topic Centre on Air Quality (ETC/AQ) has developed a concept for an air quality Model Documentation System (MDS) to be accessible on the internet. The aim of the system is to include adequate information on the individual models, their application areas, and their status with respect to evaluation and validation. Thus, a user may obtain guidance in the selection of the most appropriate model for their application. A pilot version of the MDS had been installed on the world wide web in 1997, while an updated operational version was launched in the spring of 1998. The present paper summarises the main features of the upgraded version of the MDS. Apart from fulfilling its main functional goal, i.e. to provide information on air quality models, the MDS structure also fulfils the main design goals, which are to create a lightweight, easily portable application that works through the Common Gateway Interface (CGI) and requires minimal changes in the configuration of the http server and the system files.